Associations Between Species and Habitat Niches of Macroalgae In Maitara Island Waters, North Tidore District, Indonesia - Fadel, Ariyati H.; Subur, Riyadi; Serosero, Rugaya; Abubakar, Yuyun; Abubakar, Salim; Alhadad, M Said; Susanto, Adi Noman (Jurnal Biologi Tropis, 2024)
Macroalgae have many benefits, both ecological and economic benefits for society. The ecological benefits of macroalgae that they provide habitat for several types of marine biota such as crustaceans, mollusks, echinoderms, fish or other small fish. Macroalgae on Maitara Island has a fairly high species diversity; however its existence is currently starting to experience pressure, especially due to human activities (residents) who inhabit Maitara Island. The aim of this research is to determine the types of macroalgae, and patterns of association. The methods used in this research were identify of macroalga and associations between species of organisms. Based on the research, 14 species found in Maitara Island waters, with associatoin pattern consists of 3 types such as; positive association, negative association, and non association.